Evaluation of some black cumin seed (Nigella sativa L.) genotypes in terms of quality parameters at different planting periods under Mardin ecological conditions (Revista de Investigaciones Universidad del Quindío, 2023)
This research was carried out with 3 repetitions according to the randomized blocks trial design in winter and summer planting periods of 2018-2019 and 2019-2020 in order to determine the agronomic and quality characteristics of some black cumin genotypes at different sowing periods under Mardin ecological conditions. Çameli variety and 18 different black cumin seed genotypes were used in the study and some quality parameters were examined. According to the results obtained from the research, it was determined that fatty oil ratio varied between 32.45-39.02% and fatty oil yield varied between 12.94-42.72 kg da-1 in winter planting. In summer planting; fatty oil ratio ranged between 33.99-38.13% and fatty oil yield ranged between 9.69-25.18 kg da-1. As a result of the study, it was determined that Eskişehir-5 (G9) genotype performed better than other varieties and genotypes in terms of fatty oil yield under Mardin ecological conditions. Due to the early increase in temperature in Mardin conditions, quality parameters decreased in summer planting compared to winter planting. Therefore, winter planting is recommended as the most suitable planting time for black cumin cultivation under Mardin conditions.
Keywords: Black cumin; genotype; fatty oil; thymoquinone